Artificial intelligence-augmented analysis of contemporary procedural, mortality, and cost trends in carcinoid heart disease in a large national cohort with a focus on the “forgotten pulmonic valve” - Monlezun, Dominique J.; Badalamenti, Andrew; Javaid, Awad; Marmagkiolis, Kostas; Honan, Kevin; Kim, Jin Wan; Patel, Rishi; Akhanti, Bindu; Halperin, Dan; Dasari, Arvind; Koutroumpakis, Efstratios; Kim, Peter; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background: Carcinoid heart disease is increasingly recognized and challenging to manage due to limited outcomes data. This is the largest known cohort study of valvular pathology, treatment (including pulmonary and tricuspid valve replacements [PVR and TVR]), dispairties, mortality, and cost in patients with malignant carcinoid tumor (MCT). Methods: Machine learning-augmented propensity score-adjusted multivariable regression was conducted for clincal outcomes in the 2016-2018 U.S. National Inpatient Sample (NIS). Regression models were weighted by the complex survey design and adjusted for known confounders and the likelihood of undergoing valvular procedures. Results: Among 101,521,656 hospitalizations, 55,910 (0.06%) had MCT. Patients with MCT vs. those without had significantly higher inpatient mortality (2.93% vs. 2.04, p=0.002), longer mean length of stay (12.20 vs. 4.62, p<0.001), and increased mean total cost of stay (70,252.18 vs. 51,092.01, p<0.001). There was a step-wise increased rate of TVR and PVR with each subsequent year, with significantly more TV (0.16% versus 0.01, p<0.001) and PV (0.03 versus 0.00, p=0.040) diagnosed with versus without MCT for 2016, with comparable trends in 2017 and 2018. There were no significant procedural disparities among patients with MCT for sex, race, income, urban density, or geographic region, except in 2017, when the highest prevalence of PV procedures were performed in the Western North at 50.00% (p=0.034). In machine learning and propensity score augmented multivariable regression, MCT did not significantly increase the likelihood of TVR or PVR. In sub-group analysis restricted to MCT, neither TVR nor PVR significantly increased mortality, though it did increase cost (respectively 141,082.30, p=0.015; 355,356.40, p=0.012). Conclusion: This analysis reflects a favorable trend in recognizing the need for TVR and PVR in patients with MCT, with associated increased cost but not mortality. Our study also suggests that pulmonic valve pathology is increasingly recognized in MCT as reflected by the upward trend in PVRs. Further research and updated societal guidelines may need to focus on the “forgotten pulmonic valve” to improve outcomes and disparities in this understudied patient population.